Estetika Kota dan Keterikatan Masyarakat: Analisis Pengaruh Public Art di Malioboro, Yogyakarta - Sindu Lintang Ismoyo (ATRAT: Jurnal Seni Rupa, 2025)
This study explores the role of public art in shaping community attachment to their environment and its influence on urban aesthetics, focusing on a case study of public art in Malioboro, Yogyakarta. The research employs a mixed methods approach (quantitative-qualitative) with a deductive method to analyze public perceptions of public art and its impact on public spaces. The findings indicate that public art has a positive and significant impact on place attachment, where public perception of these artworks contributes to their emotional connection with the environment. Additionally, the duration and frequency of visits influence how the public perceives public art. Further analysis reveals that public art provides significant aesthetic, social-functional, cultural, and economic benefits, including enhancing visual appeal, tourism attraction, local identity reflection, public education, and job opportunities for art practitioners. This study contributes to the understanding of the role of public art in shaping urban character and social interactions while serving as a foundation for developing policies and practices for public art in other urban areas.